Chapter 3. The Church and the Mentally Handicapped: A Continuing Challenge to the Imagination - Hauerwas, Stanley (Journal of religion, disability & health, 2005)
In this essay Hauerwas explores the experience of children with developmental disabilities and their parents. Arguing against the problemitization of disability Hauerwas asks the piercing question: What are children for? He presents a case for suggesting that the ‘problems’ that children with developmental disabilities encounter are not inherent within their condition, but rather are created by the type of society that they inhabit and the assumptions about the purpose of children within such a society. Whilst society tends to treat children as commodities which can be picked and chosen according to personal desire, Hauerwas presents a case for a theological understanding of parenting which locates responsibility for the individual child firmly within the Christian community. Children are signs of hope in the midst of a dark world. To have a child is a profound act of faith. Children, whether disabled or otherwise, are gifts given to the community. The church is constituted by those people who can take the time in a world crying with injustice to accept these Graceful gifts, some of whom may turn out to be developmentally disabled.